Latin America Report. - JOINT PUBLICATIONS RESEARCH SERVICE ARLINGTON VA (1983)
This report contains translations/transcriptions of articles and/or broadcasts from Latin America. Titles include: Impact of Heavy Rains on Rio Grande do Sul Crops Discussed; U.S. Central American Policy Scored; Economic Difficulties, IMF Aid to Chile Discussed; Problems with Los Angeles Summer Olympics Noted; Serrano Elias Reports on Meeting with Reagan, Bush; Concanaco Compares Man-Hour Costs for Basic Foods 1979, 1983; Scientific Station in Antarctic Under Consideration by Navy; Highest Inflation Rate in 60 Years; Industrial Sector in Need of Government Assistance; and others.